Estimation of Ripitability, MPPA, Livestock Ranking and The Relationship of Morning and Afternoon Milk Production in The Second and Fourth Lactation - Alhikami, Waliyyul Ahdi; Mudawamah, Mudawamah; Kentjonowaty, Inggit (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Most Producing Production Ability (MPPA), also known as Expected Production Ability (EPA) in dairy cattle, indicates the ability to produce milk that can be passed down to offspring. The objective of this study is to obtain the repeatability values of morning and evening milk production in the second and fourth lactations of Friesian Holstein (FH) dairy cows as a basis for estimating MPPA values, ranking, and the relationship of milk production in livestock. This case study uses a sample determined by purposive sampling technique, focusing on cows with recorded second and fourth lactations. The research was conducted at a local dairy farm in the Pujon area of Malang Regency. The sample consisted of 12 cows with the same day, month, and lactation period. Data were analyzed using variance analysis, correlation, and regression. The results showed that the repeatability value of morning milk production ranged from 0,63 to 0,99, categorized as high, while the repeatability of evening milk production ranged from 0,39 to 0,99, categorized as moderate to high. The MPPA values from the study ranged from 3.602 liters per cow to 10,811 liters per cow (morning milk production) and from 1,237 liters/cow to 5,024 liters/cow (evening milk production). The ranking of cattle based on MPPA morning milk production ranged from 1 to 7. The relationship between morning and evening milk production is represented by the equation Y = 0,6213, X = 1,7587 with a determination coefficient of 88,68%.